2
$\begingroup$

I'm having trouble trying proving this fact:

$\lim_{t \to \infty}t^m e^{-\alpha t} = 0$ for every $m \in \mathbb{N}$ fixed and $\alpha \in \mathbb{C}$ with $Re(\alpha) \gt 0$

I tried to use l'Hôpital's rule, but I'm not going anywhere...

$$\lim_{t \to \infty}t^m e^{-\alpha t}= \lim_{t \to \infty}\frac{e^{-\alpha t}}{\frac{1}{t^m}}=\lim_{t \to \infty}\frac{-\alpha e^{-\alpha t}}{\frac{-m}{t^{m+1}}}=\lim_{t \to \infty}\frac{\alpha ^2e^{-\alpha t}}{\frac{m(m+1)}{t^{m+2}}}=...=\lim_{t \to \infty}\frac{(-1)^n\alpha ^ne^{-\alpha t}}{\frac{(-1)^nm(m+1)\dot{}\dot{}\dot{}(m+n-1)}{t^{m+n}}}$$

$$=\lim_{t \to \infty}\frac{t^{m+n}(-1)^n\alpha^ne^{-\alpha t}}{(-1)^nm(m+1)\dot{}\dot{}\dot{}(m+n-1)}$$

EDIT Following the Hint that orion gave me I got:

$$\lim_{t \to \infty}t^m e^{-\alpha t}= \lim_{t \to \infty}\frac{t^m}{\frac{1}{e^{-\alpha t}}}$$

Since

$$ \frac{\delta^m}{\delta t^m}(t^m)=m! \quad\text{and}\quad \frac{\delta^m}{\delta t^m}\left(\frac{1}{e^{-\alpha t}}\right)=\frac{\alpha^m}{e^{-\alpha t}} $$

we have that $$\lim_{t \to \infty}\frac{t^m}{\frac{1}{e^{-\alpha t}}}=\lim_{t \to \infty}\frac{m!e^{-\alpha t}}{\alpha ^m}=0 \quad\text{since m fixed}$$

$\endgroup$
3
$\begingroup$

First of all, you're doing l'Hospital in the wrong direction. Put $t^m$ in the numerator, so that derivative actually decreases the power. Then, $m^{\text{th}}$ derivative will give you the answer you seek.

You could just as well prove that $e^{\alpha t}$ increases quicker than any finite power $t^m$. You can see that from the comparison of Taylor series.

$\endgroup$
0
$\begingroup$

$\large \lim_{t\to \infty}\dfrac{t^m}{e^{\alpha t}}$ since the limit is in the inderteminate form $\frac{\infty}{\infty}$

you can use l'hopital

$\lim_{t\to \infty}\dfrac{t^m}{e^{\alpha t}}=\frac{m}{\alpha}\lim_{t\to \infty}\dfrac{t^{m-1}}{e^{\alpha t}}=\frac{m(m-1)}{\alpha^2}\lim_{t\to \infty}\dfrac{t^{m-2}}{e^{\alpha t}}=\frac{m(m-1)(m-2)}{\alpha^3}\lim_{t\to \infty}\dfrac{t^{m-3}}{e^{\alpha t}}=...\\=\frac{m!}{\alpha^m}\lim_{t\to \infty}\dfrac{1}{e^{\alpha t}}=\frac{m!}{\alpha^m}*0=0$

since $Re(\alpha)>0$ this is valid

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.